Cultivating morphological awareness improves reading skills in fifth-grade Hebrew readers. Issue 3 (4th May 2019) - Vaknin-Nusbaum, Vered; Raveh, Michal
Abstract: The effectiveness of an intervention program aimed at improving morphological awareness was evaluated in Hebrew-speaking poor readers in Grade 5. The 12-week intervention in small groups focused on learning morphological structure of words by identifying, decomposing, and constructing morphologically complex words. Results were compared with a comparison group of similarly poor readers that participated in the school's reading support program focused on reading comprehension strategies. The intervention group improved morphological awareness to a greater extent than the comparison group and also showed a clear advantage in their reading accuracy and reading comprehension. The results suggest that morphological instruction develops awareness of the morphemic structure of words that contributes to extracting meaning from texts.